Association of bilateral acromiohumeral distance or acromion-greater tuberosity ratio with glenohumeral subluxation for stroke patients with hemiplegia based on ultrasound and radiographic techniques - Yuan, Hai; Zhang, Yan; Wang, Ting; Sheng, Mao; Chen, Luping; Shen, Lili; Ge, Pingping (Frontiers in Neurology, 2025)
IntroductionGlenohumeral subluxation (GHS) is notably a prevalent musculoskeletal issue among individuals experiencing hemiplegia following a stroke. This research seeks to assess the association between the ratio of bilateral acromionhumeral distance (AHD) or acromion-greater tuberosity (AGT) obtained via ultrasound or radiographic techniques and the severity of GHS.MethodsData were collected from bilateral measurements using ultrasonography or radiography for healthy participants based on the informed consent of each participant, and the ratio of AHDs or AGTs between the left and right sides was computed. Two measurements were employed to ascertain the reliability of the ratio. The relation of the ratio with the severity of GHS was explored based on the correlation analysis for stroke patients with hemiplegia.ResultsA total of 22 healthy participants were assessed, revealing an intra-class correlation coefficient (ICC) of 0.90 (p < 0.05) for the AGT ratio. Similarly, the ICC for the AHD ratio with 28 healthy participants, determined through radiographic evaluation, yielded an identical result of 0.93 (p < 0.05). In addition, no statistical differences in characteristics between ultrasonography and radiography groups. 47 cases of stroke patients with hemiplegia were included, and GHS was clearly diagnosed. A statistical correlation was taken between the acromio-humeral interval and the ratios in patients with stroke hemiplegia (N = 21, r = 0.56, p < 0.05 for ultrasonography and N = 45, r = 0.49, p < 0.05 for radiography).DiscussionThe ratio of bilateral AHDs or AGTs, assessed through ultrasound or radiographic method, serves as an important metric for GHS among individuals experiencing hemiplegia following a stroke, thereby facilitating focused rehabilitation strategies.